A Qualitative Study on the Implementation of Student Collaboration through Zero-Waste Activities in Group B at TK Sahabat Bekasi - Oktavianti, Dewi; Kurniawaty, Lia; Azzahri, Childa Kumala (CV. Creative Tugu Pena, 2025)
This study aims to reveal the implementation of cooperation between students in waste-free activities (zero waste) in Group B of TK Sahabat Bekasi. This research used a qualitative approach with a case study method. The subjects of this study included teachers, principals, parents, and students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, presentation, and verification techniques. The results showed that waste-free activities fostered cooperation among students through task sharing, joint responsibility, mutual help, and positive communication. The teacher’s role as a facilitator and role model was crucial, while parents supported the habit at home. This program not only instilled environmental awareness but also strengthened the socio-emotional aspects of early childhood. The study concludes that environment-based learning can effectively instill cooperation values among children.